STANDARISASI DAN UJI AKTIVITAS ANTIOKSIDAN FRAKSI AIR DAUN MURBEI (Morus alba L.) DENGAN METODE DPPH - Rizqi Noor Maulida; Yulistia Budianti Soemarie; Muhammad Fauzi (Politeknik Unggulan Kalimantan, 2025)
Excessive exposure to sunlight can lead to various skin health issues, including premature aging, as the skin serves as the body’s primary external protector. Mulberry leaves (Morus alba L.) are recognized for their content of anthocyanins and phenolic compounds, which act as antioxidant agents. This study aimed to evaluate the antioxidant effectiveness of the water fraction extracted from mulberry leaves. The research process involved collecting samples, followed by remaceration with 70% ethanol, standardization tests, and fractionation through a liquid-liquid method using n-hexane, ethyl acetate, and distilled water. The water fraction yield obtained was 6.23g. In the specific standardization tests, all parameters met the required standards; however, in the non-specific tests, the ash content exceeded the requirements, registering 10.5% above the acceptable threshold of less than 42%. Antioxidant activity was assessed using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, with quercetin as a reference. Measurement via a UV-Vis spectrophotometer revealed an IC50 value of 25.020 ± 0.223 μg/mL for the mulberry leaf water fraction, compared to an IC50 of 0.012 ± 0.009 μg/mL for quercetin, indicating that the water fraction exhibits lower antioxidant potency.